Prognostic Value of Programmed Death Ligand-1 and Human Papilloma Virus Expression in Head and Neck Squamous Cell Carcinoma - Yeniçeri, Ağah; Işık Gönül, İpek and Bilkan Öge, Ceren and Düzlü, Mehmet (ENT Updates, 2023)
Background: Human papilloma virus infection and programmed death-1/programmed death ligand-1 pathway play a role in the development of immune tolerance against the tumor. The aim of this study was to analyze the prevalence and prognostic value of human papilloma virus and programmed death ligand-1 expression in head and neck squamous cell carcinoma. Methods: The study included 73 cases with oropharyngeal and oral cavity squamous cell carcinoma. The immunohistochemistry method was used to determine p16 and programmed death ligand-1 expression. Membranous staining in tumor cells of ≥5% was considered programmed death ligand-1 positive. Human papilloma virus status, programmed death ligand-1 expression, and prognostic associations were statistically analyzed. Results: Median follow-up was 37.2 months (2-105 months). Of the total 73 patients, 61.6% (45/73) were p16 positive and 29% (21/73) were positive for programmed death ligand-1 expression by immunohistochemistry. There was no significant relationship between p16 and programmed death ligand-1 expressions (P=.62). Programmed death ligand-1 expression did not correlate with disease-free survival and overall survival (P=.62, P=.92, respectively). In regression analysis, the advanced stage (P=.011) was associated with poor overall survival, whereas p16 and programmed death ligand-1 independently did not affect overall survival (P > .05). Conclusion: There was no correlation between tumor cell programmed death ligand-1 and human papilloma virus expression in oral cavity squamous cell carcinoma and oropharyngeal squamous cell carcinoma patients, and programmed death ligand-1 was not a prognostic biomarker associated with survival. The predictive and prognostic role of programmed death ligand-1 should be supported by multicenter prospective studies with larger patient populations.